2022
DOI: 10.1002/ece3.8591
|View full text |Cite
|
Sign up to set email alerts
|

Human–wildlife conflict in the surrounding districts of Alage College, Central Rift Valley of Ethiopia

Abstract: The study was conducted between September 2018 and March 2019 to investigate the nature and extent of human-wildlife conflict (HWC) in the surrounding area of Alage College, the Central Rift Valley of Ethiopia, and to assess the perception of the local people to wildlife. For data collection, a total of 140 household (HH) heads were selected randomly for interviews from nine villages using structured and semistructured questionnaires. Moreover, focus group discussion, key informant interviews, and personal obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…The results of this review also revealed that illegal poisoning affected Canis simensis [ 45 ], which was an endangered species according to IUCN. Different nonlethal methods that are used to reduce HWC are guarding [ 33 , 40 , 41 ] with the help of dogs through chasing livestock predators [ 38 ], physical barriers like fencing [ 39 , 46 ], loud noises [ 47 ], seasonal displacement [ 33 ], fear-provoking stimuli such as scarecrows and beating drums [ 48 , 49 ], sound mechanisms for scaring [ 44 ], and repellent chemicals like scents [ 34 ]. Lethal methods used are shooting and trapping [ 34 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this review also revealed that illegal poisoning affected Canis simensis [ 45 ], which was an endangered species according to IUCN. Different nonlethal methods that are used to reduce HWC are guarding [ 33 , 40 , 41 ] with the help of dogs through chasing livestock predators [ 38 ], physical barriers like fencing [ 39 , 46 ], loud noises [ 47 ], seasonal displacement [ 33 ], fear-provoking stimuli such as scarecrows and beating drums [ 48 , 49 ], sound mechanisms for scaring [ 44 ], and repellent chemicals like scents [ 34 ]. Lethal methods used are shooting and trapping [ 34 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The respondent claimed only two incidents of lethal removal of HBB, suggesting retaliatory killing of the brown bear to reduce damage. Several studies have highlighted that the retaliatory killing of bears is a major conservation and management issue for bears in the Himalayas and elsewhere (Charoo et al, 2011 ; Rathore, 2008 ; Temesgen et al, 2022 ). The local communities have developed a negative perception of HBB due to HBC's‐associated high economic loss.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the human–HBB conflict was carried out in Lahaul valley from July 2018 to December 2019. We interviewed local communities using a semi‐structured “close and open‐ended” questionnaire to collect information on various aspects of human–HBB conflict in the study landscape (Temesgen et al, 2022 ). We also placed a total of twelve camera traps in the agriculture field and recorded the presence of HBB in the seven camera traps (Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…After stratifying the area into homogeneous groups, random sampling was conducted. Each respondent of the study settlement was selected randomly and interviewed [21,22]. Depending on the distance between the forest habitat of wild animals and the settlement area of the respondent, the distance between the forest habitat of wild animals and the settlement of the local communities was categorized as near (≤2 kilometers), medium (>2 to ≤4 kilometers), and far (>4 kilometers).…”
Section: Site Selection and Samplingmentioning
confidence: 99%
“…e questionnaire was used to explore the type and extent and causes of human-wild animal conflict, mitigation measures, livelihood characteristics of households, and local people's perceptions towards wild animal conservation. In order to gain the attention and confidence of respondents as well as to gather good information, the interviews took place at respondents' homes [22]. Participant observation in this study physically looks at what is the reality on the ground and what it made comparisons with the respondents in the household and key informant interviews.…”
Section: Primary Data Collectionmentioning
confidence: 99%